Konvergencinė žodžių daryba - Pažūsis, Lionginas (Kalbotyra, 1989)
The present paper is an attempt to treat the form of interference, generally called loan translation, as convergent word-formation, i.e. as the natural process of word-formation based on the interlinguistic analogy of the word-formative, or structural, meaning of derivatives and compounds (and even phrases) of the languages in contact. This new approach becomes particularly rewarding when we deal with loan translations (derivatives and compounds) which are traditionally considered to be not loan translation proper and when we attempt to reveal the whole scope of interference in word-formative processes. The analysis is based on the widely cited examples and those elicited from the speech of Lithuanian immigrants in America (USA and Canada).